2020
DOI: 10.3138/ptc-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoints of the Occupational Therapist Assistant–Physiotherapist Assistant Role on Inter-Professional Teams: A Mixed-Methods Study

Abstract: Purpose: Occupational therapist assistants and physiotherapist assistants work on inter-professional teams in both institutional and community settings to facilitate patients’ rehabilitation and recovery. Examination of how the assistant role is viewed by assistants and other inter-professional team members is needed to inform how to support and sustain development of the role and associated practice relationships. Method: In this explanatory sequential-design mixed-methods study, we first surveyed rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…This panel discussion met the essential Accreditation Council for Occupational Therapy Education [ACOTE] Standard (2020) requirements which are not consistently being met across programs (Penner et al, 2020). Furthermore, the results suggested that participant's learning of supervisory roles were enhanced beyond meeting essential standards, such as the soft skills which are typically gained only through time, experience, and experiential learning opportunities (Dennehy, 2022;Jung et al, 2008); which are typically thought of as possible only in the work environment (Diamant et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This panel discussion met the essential Accreditation Council for Occupational Therapy Education [ACOTE] Standard (2020) requirements which are not consistently being met across programs (Penner et al, 2020). Furthermore, the results suggested that participant's learning of supervisory roles were enhanced beyond meeting essential standards, such as the soft skills which are typically gained only through time, experience, and experiential learning opportunities (Dennehy, 2022;Jung et al, 2008); which are typically thought of as possible only in the work environment (Diamant et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Penner and colleagues (2020) described some of the challenges OTAs perceive, such as being 'left out of the loop', unclear role delineation, unclear management roles, lack of career development options, as well as internal and external norms and attitudes related to being an 'assistant'. This supervision and role delineation learning process is essential and sparsely occurs in the educational setting, resulting in entry-level occupational therapists lacking the skills to provide adequate supervision and mentoring of OTAs within their scope of roles (Penner et al, 2020). Educators have some intraprofessional collaboration opportunities in fieldwork, but collaboration between OT and OTA students within didactic coursework is limited (Carson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Hospital Not stated 19 Palmer et al (2018) 27 UK Electronic surveys Radiography 108 Assistant Practitioners Hospital Not stated 29 Pearce & Pagett (2015) 50 Australia Literature review, informal telephone and Email consultation, focus groups, online survey, semi structured interviews Multiple AHPs 36 AHAs, 23 AHA managers Allied Health Assistants; AHAs; assistants’ managers. Mixed Not stated 16 Penner et al (2020) 51 Canada Quantitative surveys and qualitative focus groups Physiotherapy; Occupational Therapy 89 for surveys (56 therapists, 37 assistants), 30 for focus groups (17 therapists, 13 assistants) Other: OTs and Physiotherapists, Occupational therapist assistants and Physiotherapist assistants Hospital Urban 28 Pinson et al (2023) 52 Australia Time motion survey and qualitative interviews Radiography 4 Medical Imaging Assistants Hospital Mixed 30 Price & Le Masurier (2007) 28 UK Quantitative, structured questionnaire Radiography 177 Radiology managers Hospital Not stated 21 Price et al (2015) 29 UK …”
Section: Resultsmentioning
confidence: 98%
“…The review found diverse literature indicating increasing reliance on and expanding scopes of practice of registered and unregistered health associate professionals [6] -in both HICs (212,(248)(249)(250)(251) and LMICs (252)(253)(254)(255). Studies focused on the HPR processes used to support a rationalization of the skills mix and allocation of roles and responsibilities, including education, management and supervision requirements to ensure safe and quality care.…”
Section: Regulation Of Scopes Of Practicementioning
confidence: 99%